Lack of host specificity of Colletotrichum spp. isolates associated with anthracnose symptoms on mango in Brazil - De Souza, A. [UNESP]; Delphino Carboni, R. C. [UNESP]; Wickert, E.; de Macedo Lemos, E. G. [UNESP]; de Goes, A. [UNESP] (Wiley, 2013)
The aim of the present study was to analyse the genetic and pathogenic variability of Colletotrichum spp. isolates from various organs and cultivars of mango with anthracnose symptoms, collected from different municipalities of São Paulo State, Brazil. Colletotrichum gloeosporioides isolates from symptomless citrus leaves and C. acutatum isolates from citrus flowers with post-bloom fruit drop symptoms were included as controls. Sequencing of the ITS region allowed the identification of 183 C. gloeosporioides isolates from mango; only one isolate was identified as C. acutatum. amova analysis of ITS sequences showed larger genetic variability among isolates from the same municipality than among those from different populations. fAFLP markers indicated high levels of genetic variability among the C. gloeosporioides isolates from mango and no correlation between genetic variability and isolate source. Only one C. gloeosporioides mango isolate had the same genotype as the C. gloeosporioides isolates from citrus leaves, as determined by ITS sequencing and fAFLP analysis. Pathogenicity tests revealed that C. gloeosporioides and C. acutatum isolates from either mango or citrus can cause anthracnose symptoms on leaves of mango cvs Palmer and Tommy Atkins and blossom blight symptoms in citrus flowers. These outcomes indicate a lack of host specificity of the Colletotrichum species and suggest the possibility of host migration. © 2012 British Society for Plant Pathology.
Keywords: Citrus spp; Colletotrichum acutatum; Colletotrichum gloeosporioides; fAFLP markers; Genetic diversity; Mangifera indica; correlation; fruit; fungus; genetic marker; genetic variation; genotype; host specificity; leaf; pathogenicity; population structure; symptom; Brazil; Sao Paulo [Brazil]; Citrus; Colletotrichum; Glomerella acutata; Glomerella cingulata